Comparing bond strength and marginal integrity with direct bulk-fill resin composites and indirect composites - Yolanda Barros; Mateus Bandéca; Andrés Millán; Fabiana Siqueira; Milton Kuga; Eduardo Fernandez; Alain Manuel Chaple Gil; Álvaro Henrique Borges; Mateus Tonetto (Editorial Ciencias Médicas, 2019)
Introduction: The clinical longevity of tooth restoration - whether directly or indirectly using composites - greatly depends on the quality and stability of the marginal adaptation. Even today, dental restoration failure is a major complication in everyday dental practice. Objective: To evaluate the effect of restoration techniques on the microtensile bond strength and marginal integrity of class II cavities. Methods: An experimental in vitro investigation was conducted. Preparations (5 × 4 × 2 mm) below the cement-enamel junction were performed in 45 human maxillary premolars (n= 15), which were the randomly selected study sample. Group G1 incrementally received Spectrum TPH3 Dentsply (De Trey) in three horizontal incremental layers. Group G2 received a bulk restoration technique (one 4-mm increment of Surefill SDR flow plus one 1-mm horizontal capping layer of Spectrum TPH3 Dentsply (De Trey) using a metal matrix band. For Group G3, impressions were made from each cavity preparation, and Spectrum was used to complete an indirect composite restoration. After storage (24 h/37 °C), the proximal surfaces of each tooth were polished with Sof-Lex disks. For microtensile bond strength testing, all premolars were sectioned into resin-dentine beams (0.8 mm2) and were tested under tension (0.5 mm/min). Results: Microtensile bond strength testing and marginal integrity values were not statistically significantly affected by the type of restoration technique used (p> 0.05). Conclusions: The Surefill SDR flow that uses a capping layer made of conventional composite can be an alternative to reduce procedure durations as well as additional steps in the restorative technique.